The Role of Immunohistochemical Expression of p63 in Atypical Proliferative Lesions and Carcinoma In Situ of the Breast - Marwa Muzahim Majeed; Ashraf M. Majeed; Ekhlas A. Ali; Nazar M. Jawhar (University of Mosul, 2024)
Background: The transcription factor p63 is a member of a family of transcription factors p53, which play a fundamental role in cell growth, multiplication, programming, differentiation and apoptosis, henceforth, aberrantly involved in the form of different variants in breast cancers. Objectives: The study aimed to determine if p63 could serve as a novel method for identifying nuclear myoepithelial cells in a normal growing cell setting for both breast cancer in situ and lesions. Methods: This study is a combination of retrospective and prospective case series analysis. It involved examining 86 samples of breast lesions obtained from private clinics and laboratories in Ninawa Province (Iraq). The study was done on the excisional biopsy, lumpectomy, and mastectomy specimens. We performed an immunohistochemical (IHC) analysis to examine the intensity of the p63 nuclear protein. The extent was scored based on the percentage of positive cells and assigned a score of negative (0%), score 1 (<25%), score 2 (26–90%), and score 3 (91-100%). Results: 61 of the 86 cases examined had benign  diagnosis, while 25 were malignant, Nuclear positivity was found in all benign lesions when using IHC staining with p63 and in the malignant cases 19 were found to be positive while 6 were negative. Conclusions: Based on the aforementioned data, we can conclude that p63 serves as a valid IHC marker for distinguishing between challenging cases, carcinoma in situ cases, cases in the grey area, and cases with an unclear histomorphological diagnosis.